Color Calibration for Arrays of Inexpensive Image Sensors - Joshi, Neel (Stanford University, 2004)
The recent emergence of inexpensive image sensors has enabled the construction of large arrays of cameras for computer graphics and computer vision applications. These inexpensive image sensors have inconsistent color responses. These inconsistencies can cause significant errors in color sensitive multi-camera applications. We present an automated, robust system for calibrating large arrays of image sensors to achieve significantly improved color consistency. We acquire images of a Macbeth color checker placed in the scene and perform gain and offset calibration on each individual sensor. This process combined with a global correction step maximizes the response range by maximizing contrast and minimizing the black level and ensures linear response that is white balanced for the scene. We present results with data acquired from 45, 52, and 95-camera arrays calibrated both indoors and outdoors for a variety of color-sensitive applications including high-speed video, matted synthetic aperture photography, and multi-camera optical flow. iii Acknowledgements This work was done primarily with Bennett Wilburn, Professor Marc Levoy, and Professor Mark Horowitz. I would like to thank all of them very much for their insight and guidance. I would also like to thank the rest of the Levoy group, particularly Vaibhav Vaish, for additional advice and assistance. I must also thank my family and friends for their endless support and for keeping me sane over the past few years. It's been fun.